The medicinal and chemical aspects of naphthoquinones isolated from Euclea natalensis A. DC. on Mycobacterium tuberculosis - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (PhD (Botany))--University of Pretoria, 2007.